Developmental psychology - Kail, Robert V. (Prentice Hall, 1993)
Providing clear connections between theory, research, and practice through consistent use of examples that tie these elements together, this best-selling text offers an authoritative exploration of psychological development - topically organized - from infancy through adolescence. It covers the cornerstones of development; learning and cognition; socialization and social skills; and perspectives from child development. For developmental psychologists and all those interested in child psychology.